Immune response in sexual inverted and non-inverted Nile tilapia fingerlings supplemented with organic acid and essential oil - Casetta, Jaísa; Gasparino, Eliane; Isabela da Silva, Caroline; Ribeiro, Ricardo Pereira; Braccini, Graciela Lucca; Refundini, Gislaine; de Souza Khatlab, Angélica; Lala, Bruno [UNESP]; Claudino-Silva, Stefania (Elsevier, 2022)
The development and intensification of tilapia farming depends on the manipulation of some physiological functions, such as the sexual inversion of larvae using a synthetic androgen (17α-methyltestosterone). This inversion, however, may represent a potential oxidative stress factor and cause damage to animals in the short, medium, and long term. Dietary supplementation of natural antioxidant compounds is an interesting alternative to combat such damage. To test this hypothesis, an experimental trial was carried out involving sexual inverted and non-inverted Nile tilapia fingerlings, both supplemented and not supplemented with a blend of organic acids and essential oils protected by microencapsulation. Animals were divided into four experimental groups: NI (non-inverted animals), I (sexual inverted animals), NI + M (non-inverted animals supplemented with microcapsules), and I + M (sexual inverted animals supplemented with microcapsules). Blood parameters (WBC - white blood cells; LY - lymphocytes; RBC - red blood cells; HGB - hemoglobin; HCT – hematocrit number; MCH - mean corpuscular hemoglobin; MCV - mean corpuscular volume and MCHC – mean corpuscular hemoglobin concentration), as well as oxidative stress markers (enzymatic activity of superoxide dismutase – SOD and catalase - CAT; and total antioxidant capacity - 2,2-diphenyl-1-picryl-hydrazyl (DPPH)) and gene expression (heat shock protein 70 kDa - HSP70) were evaluated. The HGB (p < 0.001) and HCT (p = 0.005) parameters were reduced beyond the recommended limits for the animals in group I. The MCV varied statistically between the groups (p < 0.001). However, all values were within the recommended range for the species, jointly indicating normocytic anemia in group I fingerlings at the time of collection. The activity of CAT and SOD, as well as DPPH differed statistically between the experimental groups (p < 0.001), with the lowest SOD and CAT activity, as well as the highest DPPH registered in animals supplemented with microcapsules. The expression of HSP70 was lower in I + MI animals (p < 0.001). The synergistic evaluation of the results indicates that animals sexual inverted during the larval stage have a lower total antioxidant capacity in the fingerling stage, which reflects a worsening in hematological and enzymatic parameters related to immunity; and that dietary supplementation with blend of organic acids and essential oils protected by microencapsulation is sufficient to improve the immunological response both in sexual inverted and non-inverted fingerlings.
Keywords: Enzymatic activity; Fish hematology; HSP70; Oreochromis niloticus; Protein oxidation